Utilization of Liquid Organic Fertilizer of Pineapple Waste to Improving Growth of Sweet Corn Plant in Red Yellow Podsolic Soil - Rini Suryani; Agusalim Masulili; Sutikarini Sutikarini; F. Tamtomo (International Journal of Multi Discipline Science, 2022)
This study aims to determine the effect of pineapple waste liquid organic fertilizer on the growth and yield of sweet corn in Red Yellow Podsolic soil and to obtain a dose of pineapple waste liquid organic fertilizer that can produce the highest growth and yield of sweet corn in Red Yellow Podsolic soil. This study used a completely randomized design (CRD), with 5 treatments repeated 5 times and 3 plant samples. The treatment given was in the form of a dose of liquid organic fertilizer with a dose of: P0 = 0 ml/l water, P1 = 25 ml/l water, P2 = 50 ml/l water, P3 = 75 ml/l water, P4 = 100 ml/l water. The parameters observed in this study were plant height, leaf area, root volume, soil pH, C-Organic content, N, C/N ratio and soil bulk weight. The data obtained were analyzed by fingerprint analysis of variance at the 5% level and then further tested with 5% HSD. Based on the results of the study, the dosage level of liquid organic fertilizer of pineapple waste had a significant effect on the variables of root volume and soil pH. However, it had no significant effect on the variables of plant height, leaf area, organic %C content, %N soil content, C/N ratio, and bulk density of Ultisol soil. The treatment level of liquid organic fertilizer from pineapple plant waste 50 ml/l gave the best results on the variable soil pH, and the dose of liquid organic fertilizer of pineapple plant waste 75 ml/l was the treatment that gave the best results on the variable root volume.